Model Pembelajaran Jigsaw Berbasis Game Tic-tac-toe: Kesempatan untuk Meningkatkan Konsentrasi dan Pemahaman Konseptual Siswa Materi Kimia - Nurjanah, Stevani; Suprihatiningrum, Jamil (Universitas Negeri Padang, 2024)
This study aims to determine the effect of concentration and student learning outcomes on colloidal material using a Jigsaw model infused with a tic-tac-toe game. The quasi-experimental study used a pretest and posttest nonequivalent control group design. Students in grade XI of three science classrooms in Prambanan High School were identified as the population in this study, and two of them were selected to be samples (one as a control group and another as an experimental group) using a cluster random sampling technique. While applying the Jigsaw-infused Tic-tac-toe Game, learning concentration was measured with a questionnaire. On the other hand, conceptual understanding of colloidal material was analyzed using multiple-choice tests. All data collected used statistical analysis (Mann-Whitney test for data from the questionnaire and data from the tests). The research result shows the value of sig. Questionnaire 0,002 < 0,05 and sig. Test questions 0,003 < 0,05. Based on the research results, the finding shows that applying a Jigsaw-infused Tic-tac-toe game positively affects students' concentration and conceptual understanding of chemistry.